Proses pengelolaan sampah plastik menjadi paving block di Desa Jetis, Kecamatan Kemangkon, Kabupaten Purbalingga - Alifan Nurin Anamti Dieningrum; Muslihudin Muslihudin; Edy Suyanto (Jurnal READ (Research of Empowerment and Development), 2020)
The problem of plastics - if left alone, will not rot because they are difficult to decompose and will cause environmental damage, such as flooding and environmental pollution of water and soil. Inorganic waste management can be done in various ways, one of which is through creative ideas, such as in Jetis village, Purbalingga Regency has a way to solve the problem of plastic, which is used as a paving block. This study aims to determine the process of managing plastic waste for paving blocks at “UD. Wong Cilik ”Jetis Village, Kemangkon District, Purbalingga Regency. This study used the descriptive qualitative method. research data as well as in-depth interviews, observation, namely non-participatory observation, and documentation. The research location was conducted in Jetis Village, Kemangkon District, Purbalingga Regency. The technique of taking informants was purposive sampling. The data analysis technique in this study used an interactive analysis model of Milles and Habberman. The result of this research is the beginning of "UD. Wong Cilik "was founded in 2005. The waste management carried out in Jetis Village is based on environmental considerations because it has not received assistance for TPS (temporary shelter), so finally KN has an innovative idea to create a business that utilizes plastic waste produced every day by Jetis villagers. This inorganic waste from plastic is managed into a more valuable item, namely paving blocks. The obstacle in this process is the lack of a furnace as a combustion process. The conclusion of this research is that the plastic waste management process is an innovation to solve the problem of plastic waste by making plastic waste into paving blocks.